Cerebral palsy in twins and higher multiple births: a Europe‐Australia population‐based study. (2nd February 2021) - Sellier, Elodie; Goldsmith, Shona; McIntyre, Sarah; Perra, Oliver; Rackauskaite, Gija; Badawi, Nadia; Fares, Asma; Smithers‐Sheedy, Hayley; ,
Abstract : Aim: To describe the birth prevalence, temporal trends, and clinical outcomes of twins, triplets, or quadruplets with cerebral palsy (CP). Method: This was a cross‐sectional study using data for twins, triplets, and quadruplets with prenatally or perinatally acquired CP and pooled from the Surveillance of Cerebral Palsy in Europe network (born 1992–2009) and Australian Cerebral Palsy Register (born 1993–2009). Children were at least 4 years old at time of registration. Children born in regions with population ascertainment and available denominator data were included in prevalence calculations ( n =1033 twins, 81 triplets, and 11 quadruplets). Clinical data from children registered in all participating registers were described, including 2163 twins (56% male), 187 triplets (59% male), and 20 quadruplets (45% male). Results: The birth prevalence of CP was higher with increasing plurality (twins 6.5 per 1000 live births [95% confidence interval CI 6.1–6.9], triplets 17.1 [95% CI 13.6–21.2], quadruplets 50.7 [95% CI 25.6–88.9]); however, prevalence by gestational age was similar across all pluralities. Between 1992–1994 and 2007–2009, prevalence of CP among twins declined ( p =0.001) but prevalence of CP among triplets did not change significantly over time ( p =0.55). The distributions of Gross Motor Function Classification System, epilepsy, and impairments of intellect, vision, and hearing were similar regardless of plurality. Interpretation: The data combined from two CP register networks indicated that triplets and quadruplets had increased risk of CP compared to twins. The higher prevalence of CP in triplets and quadruplets is due to their higher risk of preterm birth. Prevalence of CP among twins significantly declined in Europe and Australia. Clinical outcomes were similar for all multiple births. What this study adds: The overall prevalence of cerebral palsy (CP) was greater in triplets and quadruplets than twins. The higher prevalence of CP among triplets and quadruplets was due to their higher risk of preterm birth. Higher‐order multiples did not have more severe clinical outcomes than twins. The prevalence of CP among twins decreased over time. What this study adds: The overall prevalence of cerebral palsy (CP) was greater in triplets and quadruplets than twins. The higher prevalence of CP among triplets and quadruplets was due to their higher risk of preterm birth. Higher‐order multiples did not have more severe clinical outcomes than twins. The prevalence of CP among twins decreased over time. Video Podcast: https://youtu.be/u4IBkTqyd0I